Association between ideal cardiovascular health and bowel conditions among US adults - Wang, Yiwen; Wang, Zhigang (Frontiers in Nutrition, 2024)
Objective: The aim of this study is to explore the relationship between ideal cardiovascular health (CVH), as assessed using the Life’s Essential 8 (LE8), and bowel conditions. Methods: This cross-sectional study selected 11,108 participants aged ≥20 years from 2005-2010 National Health and Nutrition Examination Survey. LE8 scores (range 0-100) were measured according to American Heart Association definitions and were divided into health behavior and health factor scores. Bowel conditions including chronic diarrhea, constipation, and fecal incontinence were diagnosed by the Bowel Health Questionnaire. Weighted logistic regression and restricted cubic spline models were used for correlation analysis. Results: Logistic regression results showed that LE8 scores were negatively associated with chronic diarrhea and fecal incontinence, but the difference with chronic constipation was not statistically significant. The health behaviors subscale was also negatively correlated with chronic diarrhea, chronic constipation, and fecal incontinence, but health factors were negatively related to chronic diarrhea and fecal incontinence and positively related to chronic constipation. The RCS was consistent with the trend of the logistic regression findings. Sensitivity analyses reconfirmed these outcomes. Conclusions: LE8 is highly associated with chronic diarrhea and fecal incontinence, not with chronic constipation. Encouraging optimization of CVH levels may be beneficial for bowel disorders, and prevention of bowel disorders may enhance CVH.